The Management of Advanced Training of Engineering and Technical Specialists Based on the Interaction between Universities and Business-Structures - Nikitin, Aleksandr A.; Palyanov, Mikhail P.; Morozova, Marina V.; Markovichev, Aleksandr S. (International Review of Management and Marketing, 2016)
The relevance and urgency of the problem under study is defined by the significance to develop a flexible management system of advanced training of future engineering and technical specialists aimed at developing human capital assets and ensuring socio-economic development in priority guidelines of scientific and technological sector of the country. The article focuses on studying the objective necessity and matter point of the advanced vocational training, its management principles and technologies through which the model of advanced vocational training of engineering and technical specialists will be realized. The article also defines the main problems which solution will contribute to achieving the goal to develop the system of advanced vocational training of engineering and technical personnel in the field of priority guidelines realization concerning scientific and technological sector. The strategic planning of the interaction between educational organizations using network-based activities and social partners as potential employers is the leading approach of this study. The article deals with the definition of systematically important components of advanced vocational training of future engineering and technical specialists. The use of these components will help establish closer interaction between vocational training and potential employers. This study reveals objective and subjective factors affecting the management efficiency of advanced vocational training of engineering and technical personnel and defines the scope of problems relevant to education community which solution will contribute to developing efficient advanced vocational training model. This model enables engineers to achieve international vocational qualification level, high level of technological open-mindedness and offers opportunities for lifelong learning and professional retraining. The materials of the article can be useful by modeling of the advanced training of engineering and technical specialists based on the interaction between universities and business structures, the development of management mechanism of vocational education and its consolidation with world education space. Keywords: management, advanced vocational training, network forms of interaction, network-based activities, strategic planning JEL Classifications: A23, I23, I26